2021
DOI: 10.1002/cpz1.276
|View full text |Cite
|
Sign up to set email alerts
|

Protocols for Characterization of Cdk5 Kinase Activity

Abstract: Cyclin-dependent kinases (Cdks) are generally known to be involved in controlling the cell cycle, but Cdk5 is a unique member of this protein family for being most active in post-mitotic neurons. Cdk5 is developmentally important in regulating neuronal migration, neurite outgrowth, and axon guidance. Cdk5 is enriched in synaptic membranes and is known to modulate synaptic activity. Postnatally, Cdk5 can also affect neuronal processes such as dopaminergic signaling and pain sensitivity. Dysregulated Cdk5, in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 125 publications
(165 reference statements)
0
9
0
Order By: Relevance
“…Two days after the transfection, cells were treated with various inflammatory mediators. CDK5 activity was measured as previously described 34 .…”
Section: Measurements Of Cdk5 Activity In Vitromentioning
confidence: 99%
See 2 more Smart Citations
“…Two days after the transfection, cells were treated with various inflammatory mediators. CDK5 activity was measured as previously described 34 .…”
Section: Measurements Of Cdk5 Activity In Vitromentioning
confidence: 99%
“…31.543017 doi: bioRxiv preprint 3 involved in pain signaling and then can lower their threshold of activation, affect channel desensitization, or enhance channel trafficking to the plasma membrane. Of these protein kinases, Cdk5 is unusual in that it shares a high degree of homology with other Cdk's that predominately regulates the cell cycle instead of being active in post-mitotic neurons 34 . In addition, Cdk5 activity is neither induced by a cyclin, as typical with other Cdk family members, nor with a second message molecule as seen with PKA, PKC, and the Ca 2+ /calmodulindependent protein kinase CaMKII.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinase assays were performed as previously described 21 . Cdk5 was immunoprecipitated overnight from the supernatants of lysed cells using the polyclonal C-8 antibody at 4°C, and immunoglobulin isolation was performed with protein A-Sepharose beads for 2h at 4°C.…”
Section: In Vitro Cdk5 Kinase Assaysmentioning
confidence: 99%
“…6 Further studies have shown that inflammatory cytokines including tumor necrosis factor α, transforming growth factor β, and nerve growth factor can trigger ERK1/2 activation to subsequently boost p35 expression and ultimately lead to increased Cdk5 activity. 4,7,8 Cdk5 hyperactivity in primary afferent neurons has consequently been implicated with pain hypersensitivity. The transgenic overexpression of p35 alone can, in effect, promote both thermal and mechanical pain in mice.…”
Section: Introductionmentioning
confidence: 99%